Dionysus or Heracles: Mark Antony’s Religious Policy in 41 BCE in the Light of Epistula Marci Antonii Ad Koinon Asiae - Krivolapov, Gleb L. (Hyperboreus, 2023)
In 41 BCE, following the Battle at Philippi (October 42 BCE), the triumvir Mark Antony toured the eastern provinces of the Roman Republic. During this trip, he restored the authority of Rome, levied contributions upon the cities, and appointed several rulers. The analysis of several developments after the Battle of Philippi (the triumvir’s participation in Lesser Mysteries in Athens, as well as his relations with Sisinna and Cleopatra) indicates that Antony stressed his mythical ancestor Heracles several times. It follows that while Antony did not place much political value on activities relating to his role as Νέος Διόνυσος at this time, he did practice a religious policy, which at least contained some features of Heracleism based on Antony’s origin from Heracles. In Ephesus (spring 41 BCE), Antony was persuaded to grant broad privileges and immunities to the Association of Wreath-Bearers and Victors in the Sacred Games from the Inhabited World, as evidenced by his letter to the Κοινὸν τῶν ἀπὸ τῆς Ἀσίας Ἑλλήνων on the privileges of the συνόδου τῶν ἀπὸ τῆς οἰκουμένης ἱερονικῶν καὶ στεφανιτῶν. What emerges is that the letter may shed light on Antony’s religious policy during his stay in the East in 41 BCE since the association of athletes mentioned there could have some connection to Heracles. Thus, the events mentioned in the letter of Mark Antony are, with certain reservations, additional evidence in favor of the existence of Antony’s religious policy rooted in ties to his mythical ancestor Heracles during his visit to the East in 41 BCE.